Relationship between power and self direction values towards integrity practice among selected Malaysian civil servants - Kamaruddin, Nur Anis (2022)
The study used quantitative methods to investigate the relationship between power and self-direction values and integrity practice among selected Malaysian civil servants. The specific objectives of this study were to 1) determine the level of integrity practice of selected Malaysian civil servants, 2) determine the relationship between the power value and the integrity practice of selected Malaysian civil servants, 3) determine the relationship between the self-direction value and the integrity practice of selected Malaysian civil servants, and 4) determine the strength of the relationship between the power value and the value of the self-direction value. In order to have an effective impact, highlight the truth of the information, understand the value to be achieved, in accordance with the right direction, and empower accountability, effective human resource development programmes require integrity elements throughout the implementation process. The study's findings revealed an increase in integrity practices among civil servants in the study area. The study's participants also acknowledged that they had exercised integrity in all tasks completed. According to previous study, the level of integrity of a civil servant is also determined by the value held and the individual's attitude. However, the study did not investigate the factors that contributed to the improvement of civil servants' integrity practices within the organisation. The study's question is to determine the level of integrity among civil servants that can be maintained through the influence of power value and self-direction value, as well as the important factors of variables that have the relationships with integrity practices among civil servants in the public sector, as well as identify the selected variable factor that has a consistent effect on improving integrity practices among civil servants. The study was conducted at a government organisation using a convenience sampling technique, with 30 participants in the pilot study and 177 participants in the actual study. Respondents to the survey were drawn from a pool of civil servants of various ranks. The independent variables (power and self-direction values) and the dependent variable were studied using six (6) predictors (integrity practice). Data were collected using questionnaires that were distributed using the convenience sampling method. The descriptive, correlative, and regression-based analyses were carried out using a theoretical framework adapted from Schwartz's theory of planned behaviour (1992). The findings revealed that the integrity practice, power value, and self-direction value of selected Malaysian civil servants were moderate. At 0.05 significant levels, the correlation analysis revealed that the power and self-direction values had a significant positive correlation with integrity practice. Regression analysis revealed that the six (6) predictors investigated in this study (wealth, social power, authority, choosing, creating, and exploring) explained 11.1% of the variance that contributed to Malaysian civil servants' integrity practices. Under the power value, the wealth dimension (β = 0.252) was found to be the best predictor, followed by social power (β = 0.098). Meanwhile, as a determinant of the integrity practice, the choosing dimension (β = 0.069) was discovered to precede the exploring dimension (β = 0.023) under the self-direction values. As a result, this study adds to existing knowledge and understanding of issues of power and self-direction values toward integrity practice among selected Malaysian civil servants. The findings of this study should encourage more research into the motivational values that influence the practice of integrity in the public sector.